2015
DOI: 10.14802/jmd.15030
|View full text |Cite
|
Sign up to set email alerts
|

Can Postural Instability Respond to Galvanic Vestibular Stimulation in Patients with Parkinson’s Disease?

Abstract: ObjectiveGalvanic vestibular stimulation (GVS) activates the vestibular afferents, and these changes in vestibular input exert a strong influence on the subject’s posture or standing balance. In patients with Parkinson’s disease (PD), vestibular dysfunction might contribute to postural instability and gait disorders.MethodsCurrent intensity was increased to 0.7 mA, and the current was applied to the patients for 20 minutes. To perform a sham stimulation, the current intensity was increased as described and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 21 publications
1
72
0
Order By: Relevance
“…This is beginning to occur in neurological contexts, such as daily right‐ear CVS for four weeks improving aphasic syndrome in left‐hemisphere stroke and disturbed arm position sense in poststroke neglect improving with galvanic vestibular stimulation (GVS) relative to sham stimulation (note that GVS does not appear to activate ACC) . There are also reports of GVS relative to sham GVS improving autonomic, motor and other functions in Parkinson’s Disease and other central neurodegenerative disorders, and early evidence that repeated CVS for several weeks can induce behavioural improvement in the minimally conscious state . Moreover, following reports of persistent pain and allodynia modulation by CVS in case studies and small case series (discussed in Miller and Ngo 3 ; see also McGeoch et al), a recent study examined 34 subjects with persistent (mostly neuropathic) pain and found that (i) a single session of right‐ear CVS induced small but statistically significant short term modulations of pain relative to a forehead icepack cold‐arousal control condition, (ii) three of nine subjects with allodynia had large, clinically significant CVS modulations, and (iii) CVS was well tolerated, with only one subject experiencing vomiting.…”
Section: Examining the Therapeutic Efficacy Of Vestibular Neuromodulamentioning
confidence: 99%
“…This is beginning to occur in neurological contexts, such as daily right‐ear CVS for four weeks improving aphasic syndrome in left‐hemisphere stroke and disturbed arm position sense in poststroke neglect improving with galvanic vestibular stimulation (GVS) relative to sham stimulation (note that GVS does not appear to activate ACC) . There are also reports of GVS relative to sham GVS improving autonomic, motor and other functions in Parkinson’s Disease and other central neurodegenerative disorders, and early evidence that repeated CVS for several weeks can induce behavioural improvement in the minimally conscious state . Moreover, following reports of persistent pain and allodynia modulation by CVS in case studies and small case series (discussed in Miller and Ngo 3 ; see also McGeoch et al), a recent study examined 34 subjects with persistent (mostly neuropathic) pain and found that (i) a single session of right‐ear CVS induced small but statistically significant short term modulations of pain relative to a forehead icepack cold‐arousal control condition, (ii) three of nine subjects with allodynia had large, clinically significant CVS modulations, and (iii) CVS was well tolerated, with only one subject experiencing vomiting.…”
Section: Examining the Therapeutic Efficacy Of Vestibular Neuromodulamentioning
confidence: 99%
“…The studies about VEMP with auditory stimulation have evidenced this test as an assisting tool for the diagnosis of several types of peripheral vestibular disorders, predominantly Meniere's disease (5,6,29,40) and superior semicircular canal dehiscence (SSCD) (8)(9)(10)(11)32) , as well as diseases related to central vestibular disorders, such as motor myelopathies (19)(20)(21)(22)(23)(24)(25) and Parkinson's disease (15,(41)(42)(43) .…”
Section: Discussionmentioning
confidence: 99%
“…There may be a preference for backward (retropulsion), forward (propulsion) or lateral (lateropulsion) pulsion. Increases in the time of double support and reduced walking speed occur [7,8]. The so-called tunnel effect consisting in taking small steps before a narrowing along a path of movement also takes place.…”
Section: Introductionmentioning
confidence: 99%